Biomarkers of Alzheimer's disease and mild cognitive impairment: a current perspective - Lewczuk, Piotr; Mroczko, Barbara; Fagan, Anne; Kornhuber, Johannes (Advances in Medical Sciences, 2015)
A growing body of evidence supports the application of the neurochemical dementia diagnostics (NDD) biomarkers for the diagnosis of dementing conditions. Biomarkers of Alzheimer's disease (AD) were recently classified as these reflecting amyloid ? pathology (decreased CSF concentrations of A?42 and/or positive A? PET scan) and these reflecting neurodegeneration (increased CSF Tau concentrations, decreased uptake of FDG on FDG-PET, and cerebral atrophy on structural MRI). Particularly important seems the role of the biomarkers in the early diagnosis of AD, as the first pathophysiologic events observable in the CSF and amyloid ?-PET occur years and perhaps decades before the onset of the earliest clinical symptoms. Therefore, the NDD tools enable the diagnosis of AD already in the early preclinical stage. This review summarizes pathophysiology underlying the CSF biomarkers, following a discussion of their role in the current guidelines for the diagnostic procedures.
EVALuna2:23713